178 caveolin-3 A Novel Regulator of Ryanodine Receptor; A Relationship that is Perturbed in the Obese Heart. (3rd June 2016) - Iqbal, Mohammad Monib; Bennett, Hayley J; Davenport, Bernard; Bussey, Charlotte; Cartwright, Elizabeth; Kitmitto, Ashraf
Abstract : Background: Obesity is the leading cause of insulin resistance and a key factor underlying the development of type 2 diabetes. 1 Impaired excitation-contraction (EC) coupling is a hallmark of both type 1 and type 2 diabetes. 2 EC coupling is maintained by the finely tuned process termed calcium induced calcium release involving a number of proteins including the ryanodine receptor (RyR2). Our group has previously reported an interaction between caveolin-3 (Cav3) and RyR, 3 however, the functional consequences of this interaction are unknown. Cav3, a small integral membrane protein is involved in orchestrating an array of signalling pathways and is a negative regulator of nitric oxide synthase (NOS) and thus nitric oxide (NO) production. Significantly, post-translational modification of RyRs, S-nitrosylation, the addition of nitroso group, has been linked to 'leaky' channels. We hypothesize that the formation of a Cav3-RyR2 complex has a cardioprotective role regulating NOS activity within cardiac myocytes by maintaining the nitroso-redox state of the receptor and that this relationship is perturbed in the obese heart. Methods: Tissue was lysed from the left ventricle fromrats fed a high fat diet (40% HFD) and age-matched control rats on normal chow (10% diet) and probed for protein expression levels using western blotting. The SPRY domain of RyR2 was recombinantly expressed and purified from E.coli, and recombinant full length Cav3 was expressed and purified from yeast ( Pischia Pastoris ). Interaction between full-length recombinant Cav3 and SPRY domain was analysed by microscale thermophoresis (MST). Results: In the pre-diabetic heart (obesity) we have determined a down-regulation of Cav3 expression (P < 0.05), elevated levels of NOS3 (P < 0.01) but no change to RyR2 levels in the left ventricle. Our bioinformatics analyses identified multiple putative caveolin binding motifs (CBMs) within the RyR1 and RyR2 primary sequences that are conserved. The recent publication of a high resolution 3-D structure of skeletal RyR1 allowed us to determine that one of the CBMs is localised to a SPRY domain and sequence alignment with RyR2 found this region is conserved. We have successfully purified the RyR2 SPRY domain and full-length Cav3. Preliminary data indicate a possible interaction between recombinant Cav3 and the SPRY domain using microscale thermophoresis. Conclusion: Our study shows down-regulation of Cav3 and upregulation of NOS3 with no change in RyR2 expression level in the obese rat model. Functional studies are now underway to investigate the implications of an imbalance between NOS3 and Cav3 in terms of RyR2 calcium release. Further, biophysical and structural studies are now necessary to investigate the putative SPRY-Cav3 interaction and determine if other regions of RyR2 mediate Cav3-RyR2 binding. References: Klein, R. Hyperglycemia and microvascular and macrovascular disease in diabetes. Diabetes Care. 1995;18:258-–68 Cesario, D. A., Brar, R. & Shivkumar, K. Alterations in ion channel physiology in diabetic cardiomyopathy. Endocrinol Metab Clin North Am, 2006;35:601-–10, ix–x Whiteley, G., Collins, R. F. & Kitmitto, A. Characterisation of the molecular architecture of human caveolin-3 and interaction with the skeletal muscle ryanodine receptor. J Biol Chem. 2012;287:40302–16